1988
DOI: 10.1093/carcin/9.6.931
|View full text |Cite
|
Sign up to set email alerts
|

Reversal by ribo- and deoxyribonucleosides of dehydroepiandrosterone-induced inhibition of enzyme altered foci in the liver of rats subjected to the initiation-selection process of experimental carcinogenesis

Abstract: The effect of dehydroepiandrosterone (DHEA) on the activity of NADPH-producing enzymes and the development of enzyme-altered foci has been investigated in the liver of female Wistar rats subjected to an initiating treatment (a necrogenic dose of diethylnitrosamine) followed, 15 days later, by a selection treatment [a 15-day feeding of a diet containing 0.03% 2-acetylaminofluorene (2-AAF), with a partial hepatectomy at the midpoint of this feeding]. At the end of the selection treatment all rat groups received,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…G6PDH was not only more active in the liver of untreated females compared to males but was also induced more strongly in females by DHEA treatment. This agrees with our previous findings (Mayer et al, 1996) but is at variance with the data of Garcea et al (1988), who observed a decrease in G6PDH activity in liver homogenates from female rats treated for 2 weeks with 0.6% DHEA in the diet. The strong increase in ME activity is in accordance with observations of different investigators (Garcea et al, 1988;Cleary, 1990).…”
Section: Dhea Effect On Metabolic Key Enzymes Of Rat Liversupporting
confidence: 93%
“…G6PDH was not only more active in the liver of untreated females compared to males but was also induced more strongly in females by DHEA treatment. This agrees with our previous findings (Mayer et al, 1996) but is at variance with the data of Garcea et al (1988), who observed a decrease in G6PDH activity in liver homogenates from female rats treated for 2 weeks with 0.6% DHEA in the diet. The strong increase in ME activity is in accordance with observations of different investigators (Garcea et al, 1988;Cleary, 1990).…”
Section: Dhea Effect On Metabolic Key Enzymes Of Rat Liversupporting
confidence: 93%
“…By using DHEA in combination with an initiation/selection model of hepatocarcinogenesis (Solt-Farber-protocol) that results in a large number of rapidly proliferating nodules, Garcea et al (9) observed a reduction of G6PDH activity in total liver postmitochondrial supernatant and a reduction in the number of GGT-positive liver lesions by DHEAtreatment. The same authors (6,8) reported an inhibition of [ 3 H]-thymidine incorporation and a reduction of mitotic index in rapidly proliferating hepatic nodules induced in female Wistar rats. The inhibition of thymidine incorporation could be reversed by the injection of ribo-and deoxyribonucleosides (8).…”
Section: Anticarcinogenic Effect Of Dheamentioning
confidence: 93%
“…The same authors (6,8) reported an inhibition of [ 3 H]-thymidine incorporation and a reduction of mitotic index in rapidly proliferating hepatic nodules induced in female Wistar rats. The inhibition of thymidine incorporation could be reversed by the injection of ribo-and deoxyribonucleosides (8). The authors conclude that DHEA inhibits formation of preneoplastic lesions by the reduction of G6PDH activity resulting in a depletion of the tissue in ribo-and deoxyribonucleotides.…”
Section: Anticarcinogenic Effect Of Dheamentioning
confidence: 93%
“…The chemoprotective and anti-proliferative actions of DHEA have been explained by several mechanisms, including the inhibition of glucose-6-phosphate dehydrogenase, 9,31,32 the suppression of farnesyl diphosphate and the cholesterol biosynthetic pathway via the inhibition of HMG-CoA reductase, 7,10,33 direct interference with the mitogen-activated protein kinase (MAPK) pathway, 34,35 and the suppression of nitric oxide generation, through downregulation of nitric oxide synthase II (iNOS). 36,37 However, it is possible that other mechanisms that have yet to be discovered also play a role in the anti-carcinogenic effects of DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Induction of cell-cycle arrest by DHEA treatment has also been demonstrated in the human colonic adenocarcinoma cell line, HT-29 7 and in Ehrlich's tumor cells. 8 These effects of DHEA have not been explained completely, and several mechanisms, including the depletion of nicotinamide adenine dinucleotide phosphate, reduced (NADPH) and ribose-5-phosphate, due to the inhibition of glucose-6-phosphate dehydrogenase (G6PD) activity, 9 and suppression of the cholesterol biosynthetic pathway by the inhibition of 3-hydroxy-3-methylglutaryl-CoA (HMG)-CoA reductase (HMGR) activity, 10 would appear to contribute to these actions. However, a previous study by ourselves demonstrated that many DHEA-related steroids inhibited the activities of both these enzymes, but that the inhibition of cell growth did not correlate with inhibition of either enzyme activity.…”
Section: Introductionmentioning
confidence: 99%